Analysis of Physiological and Psychological Workload Using the Cardiovascular Load Method and Rating Scale Mental Effort in Members Police Satreskrim Polresta Gorontalo City - Tarisa Ramadhani Gobel; Herlina Jusuf; Ayu Rofia Nurfadillah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Members of the Criminal Investigation have a tough task in dealing with physical and mental demands during investigations and investigations, thus contributing to the emergence of a high workload. The purpose of the study was to analyze physiological and psychological workload using the Cardiovascular Load and Rating Scale Mental Effort methods in members of the Gorontalo City Police Satreskrim Police. This type of research uses a descriptive research design, where data was collected through measuring workers' pulse from the CVL method and data from the RSME questionnaire on 35 samples of members of the Gorontalo City Police Satreskrim. The results of the CVL and RSME analysis for the physiological and psychological workload level of 35 members, showed that the physiological load of 25 members needed to be improved (30% to 60%) while 10 members did not experience fatigue (30%). At the level of Psychological workload, there were 4 members with a large effort (86-100), 9 members with a very large effort (101-114) and 22 members with a very large effort (115-150). The results of the calculation of physiological and psychological workload were proposed to increase the number of workers because they experienced a high workload. Police institutions are advised to conduct periodic evaluations to manage the physiological and psychological workload of satreskrim members, so that they remain optimal.